Specific structure, biology, population ecology H. bovis and H. lineatum in the steppe zone of Stavropol territory - I. O. Lysenko (Юг России: экология, развитие)
Are studied specific structure, features of biology and population ecology H. bovis and H. lineatum in a steppe zone of Stavropol Territory. Character of spatial distribution of larvae is established. The factors defining processes of regulation of number in populations of activators hipodermatoz are defined.